PENGARUH KUALITAS PRODUK,BRAND AWARENESS,DAN DAYA TARIK IKLAN PRODUK JAMU TOLAK ANGIN SIDO MUNCUL TERHADAP KONSUMEN PADA MASA PANDEMI COVID 19 - Widodo, Herry; Wiku, Victor (STIE PENA, 2023)
This research is entitled “The Influence of Product Quality, Advertising Attractiveness and Brand Awareness on Consumer Satisfaction of Tolak Angin Sido Products Appearing During the Covid 19 Pandemic. Appeared During the Covid 19 Pandemic. The sampling method used was Nonprobability sampling. The population in this study were 190 students of the Faculty of Economics, Muhammadiyah University, Semarang. The sample in this study were 80 students from the Faculty of Economics, Muhammadiyah University, Semarang. The data analysis method was carried out using quantitative data analysis. Quantitative analysis includes validity test, reliability test and classic assumption test, multiple linear regression analysis, t test and F test, analysis of the coefficient of determination (R1), and using the SPSS. Product quality (X1) has no significant effect on consumer satisfaction (Y), this is evidenced by a tcount of 0.488 ≤ ttable of 1.991 with a significance probability value of 0.627 > 0.05 (α). Advertising attractiveness (X2) has a positive and significant effect on consumer satisfaction (Y), this is evidenced by a tcount of 6.235 > ttable of 1.991 with a significance probability value of 0.00 ≤ 0.05 (α). Brand Awareness (X3) has a positive and significant effect on consumer satisfaction (Y), this is evidenced by a tcount of 2.358 > ttable of 1.991 with a significance value of 0.021 <0.05 (α). Product Quality (Xı), Price (X2) and Location (X3) jointly (simultaneously) have a positive and significant effect on Purchase Decision (Y), this is evidenced by the Fcount value of 59,607 > Ftable of 2.72 with a significance value a = 0.000 (0%) < 0.05 (5%). Thus (H4) states that Product Quality, Advertising Attractiveness and Brand Awareness jointly (simultaneously) have a positive and significant effect on consumer satisfaction (Y) is accepted. The results of the regression equation are: Y=4.912 + 0.042X1 + 0.730X2 + 0.244X3 + e. The value of the coefficient of determination is indicated by the R-Square value of 0.702 which indicates that the variables Product Quality (X1), Advertising Attractiveness (X2) and Brand Awareness (X3) together (simultaneously) can explain the purchase decision of 70.2 % while the remaining 30.8% is explained by factors not examined in this study.Keywords: Product Quality, Advertising Attractiveness, Brand Awareness, Purchase Decision